Need help from an expert?
The world’s top online tutoring provider trusted by students, parents, and schools globally.
The identity for hyperbolic cosine is derived using the exponential function and its properties.
The hyperbolic cosine function is defined as cosh(x) = (e^x + e^-x)/2. To derive its identity, we start with the definition of cosh(x) and its derivative:
cosh(x) = (e^x + e^-x)/2
cosh'(x) = sinh(x) = (e^x - e^-x)/2
We can use the properties of the exponential function to simplify these expressions. First, we note that e^x * e^-x = 1, so we can multiply the numerator and denominator of cosh(x) by e^x to get:
cosh(x) = (e^2x + 1)/(2e^x)
Similarly, we can multiply the numerator and denominator of sinh(x) by e^x to get:
sinh(x) = (e^2x - 1)/(2e^x)
Now we can use these expressions to derive the identity for cosh^2(x) - sinh^2(x). We start with:
cosh^2(x) - sinh^2(x) = (e^2x + 1)^2/(4e^2x) - (e^2x - 1)^2/(4e^2x)
Simplifying this expression gives:
cosh^2(x) - sinh^2(x) = (e^4x + 2e^2x + 1 - e^4x + 2e^2x - 1)/(4e^2x)
cosh^2(x) - sinh^2(x) = 2e^2x/4e^2x
cosh^2(x) - sinh^2(x) = 1
Therefore, we have derived the identity cosh^2(x) - sinh^2(x) = 1, which is a fundamental property of hyperbolic functions.
Study and Practice for Free
Trusted by 100,000+ Students Worldwide
Achieve Top Grades in your Exams with our Free Resources.
Practice Questions, Study Notes, and Past Exam Papers for all Subjects!
The world’s top online tutoring provider trusted by students, parents, and schools globally.